John Clement Fitzpatrick papers - Fitzpatrick, John Clement, 1876-1940.
Chiefly correspondence relating to The Writings of George Washington from the Original Manuscript Sources, 1745-1799 (1931-1944) edited by Fitzpatrick, together with card files indexing the work; speeches by Fitzpatrick; notes and drafts relating to a study of Virginia colonial governors; and other papers and reference files. Subjects include George Washington and his family; Washington's estate, Mount Vernon, Va.; and the George Washington Bicentennial Commission. Other topics include the Military Order of the Purple Heart, history of New Jersey during the American Revolution, Declaration of Independence, sesquicentennial of the U.S. Constitution, and the papers of Washington's aide, Tobias Lear.
Correspondents include Randolph Greenfield Adams, Maxwell Anderson, George A. Ball, Sol Bloom, Julian P. Boyd, Roy Bird Cook, Francis Pendleton Gaines, Curtis Wiswell Garrison, Louis F. Gottschalk, U.S. Grant, Albert Bushnell Hart, Archibald Henderson, Rupert Hughes, J. Franklin Jameson, David Maydole Matteson, Samuel Eliot Morison, Elwin L. Page, Victor Hugo Paltsits, Josiah Harmar Penniman, William H. Richardson, James Alexander Robertson, Ernest Spofford, E.G. Swem, Alexander J. Wall, Charles Cecil Wall, Bernhard Wolf Weinberger, and Henry Woodhouse.
Archivist, librarian, historian, and editor. Acting chief of the Library of Congress Manuscript Division and historical editor of the writings of George Washington.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Collection related to the Library of Congress Archives.
Keywords: Adams, Randolph Greenfield, -- 1892-1951 -- Correspondence; Anderson, Maxwell, -- 1888-1959 -- Correspondence; Ball, George A. -- Correspondence; Bloom, Sol, -- 1870-1949 -- Correspondence; Boyd, Julian P. -- 1903-1980 -- Correspondence; Cook, Roy Bird, -- 1886-1961 -- Correspondence; Fitzpatrick, John Clement, -- 1876-1940; Gaines, Francis Pendleton, -- 1892-1963 -- Correspondence; Garrison, Curtis Wiswell, -- 1901- -- Correspondence; Gottschalk, Louis F. -- 1869-1934 -- Correspondence; Grant, U. S. -- 1881-1968 -- Correspondence; Hart, Albert Bushnell, -- 1854-1943 -- Correspondence; Henderson, Archibald, -- 1877-1963 -- Correspondence; Hughes, Rupert, -- 1872-1956 -- Correspondence; Jameson, J. Franklin -- 1859-1937 -- Correspondence; Lear, Tobias, -- 1762-1816.; Matteson, David Maydole, -- 1871-1949 -- Correspondence; Morison, Samuel Eliot, -- 1887-1976 -- Correspondence; Page, Elwin L. -- 1876- -- Correspondence; Paltsits, Victor Hugo, -- 1867-1952 -- Correspondence; Penniman, Josiah Harmar, -- 1868-1941 -- Correspondence; Richardson, William H., -- 1864-1937 -- Correspondence; Robertson, James Alexander, -- 1873-1939 -- Correspondence; Spofford, Ernest -- Correspondence; Swem, E. G. -- 1870-1965 -- Correspondence; Wall, Alexander J. -- 1884-1944 -- Correspondence; Wall, Charles Cecil -- Correspondence; Washington, George, -- 1732-1799.; Washington, George, -- 1732-1799 -- Family; Weinberger, Bernhard Wolf, -- 1885-1960 -- Correspondence; Woodhouse, Henry, -- 1884- -- Correspondence; Washington family; United States; George Washington Bicentennial Commission (U.S.); Library of Congress -- Officials and employees; Military Order of the Purple Heart; Dwellings -- Virginia; Governors -- Virginia; Medals, Military and naval -- United States; Plantations -- Virginia; Mount Vernon (Va. : Estate); New Jersey -- History -- Revolution, 1775-1783.; Virginia -- Politics and government -- To 1775.; Archivists; Editors; Historians; Librarians